Renewable Energy and Sustainable Development and Their Relation with Remote Sensing - Farouk EL Baz (Renewable Energy and Sustainable Development)
It is with pleasure that I welcome this initiative of the Arab Academy of Science and Technology (AASTMT). I applaud the AASTMT for emphasis on the applications of renewable energy to sustainable development. This new journal will assist in popularizing the significance of this important effort. Because the topic is rather new to many developing countries, emphasis is to be placed on communicating the significance of the endeavor. Thus, scientists and technologists should attempt to convey the expected benefits to the society at large. Articles and case studies in this new journal will be case studies in an easy to follow explanation of the proper procedures and their expected benefits. There is no limitation to subjects that would have an impact on the topic. For example, my own field of studying the earth with data collected from space would have an impact. For example, the potential use of satellite image data to the selection of sites for the generation of solar energy. This would be based on the topography, measurements of the aridity index, and preferred locations near large cities, as well explained by Dr. Hany El-Nokrashi in this volume. It is clear that in Egypt and throughout the Arab world there is a need to emphasize the use of solar energy. Our region includes some of the driest places on Earth. The impinging solar radiation during most of the year would be invaluable to the production of all energy needs. In addition, many regions are endowed with utilizable wind for the production of additional energy. The use of such research would go a long way in sustaining a clean environment for a vast number of citizens. For these reasons, I congratulate all those who embarked on bringing this valuable effort to fruition. It is particularly significant that many participants in this effort represent younger generations of Egyptians. I applaud you all and wish you continued success.